PENGARUH KECERDASAN EMOSIONAL, PERILAKU BELAJAR, DAN MINAT BELAJAR TERHADAP TINGKAT PEMAHAMAN AKUNTANSI MAHASISWA DI YOGYAKARTA: THE EFFECT OF EMOTIONAL INTELLIGENCE, LEARNING BEHAVIOR, AND LEARNING INTEREST ON STUDENT ACCOUNTING UNDERSTANDING LEVEL IN YOGYAKARTA - Prastika, Anjar; Widodo, Sri (CURRENT: Jurnal Kajian Akuntansi dan Bisnis Terkini, 2023)
The level of understanding of accounting is very important because it can know the knowledge that has been obtained during lectures to equip it to become an accountant so that it can carry out the role of the accounting profession in the business world. This study aims to determine the effect of emotional intelligence, learning behavior, and interest in learning on the level of understanding of accounting in students. Data collected in research throught online questionnaires. Sampling used a purposive sampling technique with the criteria of accounting students in semester 7 whose accounting study program has been accredited A and Unggul; taking or has taken courses in introduction to accounting, intermediate financial accounting, advanced financial accounting, auditing, and accounting theory. The sample of this study was 113 active students of the Accounting Study Program at UPY, UTY, UMY, UMBY, UAJY, UII, UST, UGM, UNY, UPNVY, and STIE YKPN Yogyakarta. Data analysis techniques using multiple linear regression models. This study shows that emotional intelligence affects the level of understanding of accounting, while learning behavior and interest learning do not affect the level of understanding of accounting